The thinking styles among the students of the National Center for the Distinguished – Comparative study in lattakia city (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The research aimed to know the styles of thinking among students of the National Center for the Distinguished. The sample of the research was chosen intentionally , it composed of students from grade students secondary school in " National Center for the Distinguished ", The research had the analytical descriptive method, and it used list from ways of thinking prapard by the searcher. The study showed that the most common for ways of thinking among the students of the National Center for the Distinguished were legislative, thinking and then executive and external, while the lowest common were minorities thinking and conservative and monarchy, and the study showed that: there was not a statistically significant difference between the students of the National Center male and excelling in all ways of thinking. . As the study showed that there was not a statistically significant difference between the students of the National Center , exceapt global thinking style and monarchy thinking styles.